(untitled) (Indian Journal of Public Health Research & Development, 2026)
Background: Chrono-nutrition explores the role of meal timing, frequency, and regularity in shaping metabolic health through circadian mechanisms. Evidence indicates that glucose metabolism, insulin secretion, and appetite regulation follow circadian rhythms and are influenced by the temporal distribution of energy intake. Late or evening-skewed eating patterns and circadian misalignment, common in modern lifestyles, are associated with poorer metabolic outcomes. This study examined the association between meal timing, percent body fat, blood glucose, and insulin levels in adolescents and young adults (16-25 years old). Methods: Of 1,313 apparently adolescents and young adults screened, complete data were available for 1,015 participants after applying predefined exclusion criteria. Body composition was assessed using bioelectrical impedance, while fasting and 2-hour post-glucose blood samples were analysed for plasma glucose, insulin, and HbA1c using standard methods. Meal timing was recorded based on the last meal consumed the previous night, and data were analysed using SPSS 27 with p<0.05 considered statistically significant. Results: Among the 1,015 participants, 42.6% were males and 57.4% females, with 41.2% aged 16–18 years and 58.8% aged 19–25 years. The mean time of the last meal was 20.57 ± 1.10 h, ranging from 17:00 to 23:30 h. Later meal timing was associated with significantly higher percent body fat, while muscle mass was significantly greater among those who consumed their last meal earlier. Participants in the earliest meal-timing quintile had significantly lower stimulated glucose, fasting and post-glucose insulin levels, and HOMA-IR compared with later quintiles. Time of last meal showed positive correlations with percent body fat, glucose and insulin indices, and a negative correlation with muscle mass. Conclusion: Late timing of the last meal was associated with higher insulin levels, increased adiposity, and poorer metabolic profiles among adolescents and young adults. These findings suggest that eating patterns misaligned with circadian rhythms may predispose metabolically healthy youth to future metabolic risk. Promoting earlier meal timing and appropriate redistribution of energy intake during waking hours may serve as a feasible strategy for metabolic health prevention.